'Ain't nobody gonna mess with us': Understanding orality through online fanfiction. (14th April 2017) - Marone, Vittorio; Neely, Anthony
Abstract : Fanfiction is a work of fantasy in which fans write stories based on original books, movies, TV series, and other cultural and artistic forms of expression. This study looks into fanfiction dedicated to the popular TV series Breaking Bad. In particular, it examines how fans construct the (spoken) dialogues of their (written) stories. The article explores the pedagogic value of using fanfiction in educational contexts, focusing on the analysis, creation, and enactment of stories inspired by TV series and movies that feature a combination of narration and 'written speech'. The article also offers practical recommendations for classroom and online activities that support the development of skills and understandings related to writing and orality. The effort of representing speech in a written form (i.e., writing dialogues and descriptions of conversations) can help students reflect, with the aid of the teacher, on the distinctiveness and specificity of written and spoken communication. By comparing, contrasting, and critiquing audiovisual and written texts (e.g., the episodes of a TV series and the transcriptions of its dialogues), and by creating their own dialogue-rich stories, students can improve their understanding of the idiosyncrasies of writing and orality across modes, thus advancing their literacy and critical skills as creative producers, not just consumers, of popular culture and media.